The new post-oil arab gulf : managing people and wealth - Sultan, Nabil; Weir, David; Karake-Shalhoub, Zeinab ([S.l.] : Saqi Books, 2011)
The sharp increase in oil revenues since 2002 has left the Arab Gulf States with billions of petro-dollars. But how will these countries fare in the post-oil era? The rulers of these states are taking serious measures to ensure the survival of their economies, and indeed their regimes, in a world with scarce mineral resources. This book explores the extent to which these countries have been and will be able to prepare for the future by transforming themselves into serious international destinations for tourism, finance, healthcare, and education. It also considers the implications of failure for the future survival of their regimes. Topics covered include sovereign funds, Islamic finance, new technologies, higher education, and the role of women. A timely study into this vibrant and important region, this book will provide food for thought for academics, policy makers, and general readers. Nabil Sultan is a senior lecturer at the Liverpool Hope University. David Weir is a professor at Liverpool Hope University. Zeinab Karake-Shalhoub is director of research at the Dubai International Financial Centre in the United Arab Emirates.